2001
DOI: 10.1542/peds.108.2.e32
|View full text |Cite
|
Sign up to set email alerts
|

Syndromic Ear Anomalies and Renal Ultrasounds

Abstract: ABSTRACT. Objective. Although many pediatricians pursue renal ultrasonography when patients are noted to have external ear malformations, there is much confusion over which specific ear malformations do and do not require imaging. The objective of this study was to delineate characteristics of a child with external ear malformations that suggest a greater risk of renal anomalies. We highlight several multiple congenital anomaly (MCA) syndromes that should be considered in a patient who has both ear and renal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(89 citation statements)
references
References 32 publications
3
76
1
9
Order By: Relevance
“…After patients with syndromic diagnoses are excluded from the analysis, Leung and Robson in Calgary, Canada, carried out a prospective study to investigate the incidence of renal anomalies associated specifically with preauricular sinuses and concluded such anomalies were significantly more common in patients with a preauricular sinus than the 1% incidence of renal anomalies reported in the general population and advised renal ultrasound in all cases of preauricular sinuses. Wang et al in California, U.S.A, refined Leung's indications for renal ultrasound [7,8]. They suggested that renal ultrasound should only be performed on patients with a preauricular sinus and one or more of the following:…”
Section: Managementmentioning
confidence: 99%
“…After patients with syndromic diagnoses are excluded from the analysis, Leung and Robson in Calgary, Canada, carried out a prospective study to investigate the incidence of renal anomalies associated specifically with preauricular sinuses and concluded such anomalies were significantly more common in patients with a preauricular sinus than the 1% incidence of renal anomalies reported in the general population and advised renal ultrasound in all cases of preauricular sinuses. Wang et al in California, U.S.A, refined Leung's indications for renal ultrasound [7,8]. They suggested that renal ultrasound should only be performed on patients with a preauricular sinus and one or more of the following:…”
Section: Managementmentioning
confidence: 99%
“…Any association between the abnormalities of these two organs is therefore unlikely due to a single insult but rather represents the effects of a common gene or a prolonged toxic insult hence there is increased frequency of clinically significant renal anomalies in association with ear malformations when that latter are a constituent of multiple congenital anomalies syndromes such as CHARGE association, Branchio-oto-renal (BOR) syndrome, TownesBrocks syndrome, or in diabetic embryopathy [1,5].…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal abnormalities associated with microtia or anotia include trisomy 21, trisomy 18, trisomy 13, and the deletion complexes 18q-, 18p-, and 5p- (Harris et al, 1996;Carey, 1993;Buyse, 1990). Other birth defects associated with microtia/anotia include holoprosencephaly, facial clefts, cardiac defects, anophthalmia/microphthalmia, esophageal atresia, limb reduction deformities, renal anomalies, polydactyly, and vertebral anomalies (Wang et al, 2001;Harris et al, 1996;Mastroiacovo et al, 1995).…”
Section: Discussionmentioning
confidence: 99%